Prevalence of peripheral arterial disease among patients with acute coronary syndrome, a sample of Iraqi patients in Al-Yarmook Teaching Hospital 2016 - Altaei, Osama A.; Al-Sharifi, Abbass N. (Journal of the Faculty of Medicine Baghdad, 2021)
AbstractBackground: A significant proportion of patients with ischemic heart disease have been associated with peripheral arterial disease, yet it is still underestimated by our health system as many of patients are asymptomatic and this condition remains under diagnosed and therefore undertreated.Objective: To study prevalence of peripheral arterial disease of the lower limbs in patient with acute coronary syndrome and its association with certain risk factors.Method: A cross sectional descriptive study was conducted in the coronary care unit at Al-Yarmouk Teaching Hospital from the 1st of January 2016 to the 1st of November 2016 where hundred and fifty (150) patients enrolled to the coronary care unit with approved acute coronary syndrome, had been evaluated for peripheral arterial disease by assessing Demographic, risk factors and clinical features of the patients, including age groups, gender, hypertension, diabetes mellitus, smoking, dyslipidemia, family history. of coronary artery disease, previous history of cerebrovascular accident, body mass index, leg pain, measurement of ankle brachial index using hand held continuous wave Doppler device.Results: in 150 acute coronary syndrome patients were included male were (70.7%) , peripheral arterial disease was found in 31.2% through measuring ankle brachial index, 51% of those patients were asymptomatic and 29.8% with atypical leg pain and 12.8% with intermittent leg pain and 6.4% had pain at rest. And ankle brachial index in the 150 patients with acute coronary syndrome were 68.8% normal (ankle brachial index =1.4-0.91) and 21.3% (ankle brachial index =0.9-0.71) and 7.3 %( ankle brachial index =0.69-0.41) and 2.6% (ankle brachial index ≤0.40). Factors independently related to peripheral arterial disease were old age (>60 years) which constitutes 51% and p value was 0.013, and smoking which constitutes 46.8% and P value was 0.04, and dyslipidemia which constitutes 74% and P value was 0.03, and finally previous history of cerebrovascular accident which constitutes 21.2% and P value was 0.0018.Conclusion: The prevalence of peripheral arterial disease in patients presenting with acute coronary syndrome is considerable and significant, the majority of patients were asymptomatic, it is associated with increased cardiovascular risk. Factors like aging, hypertension, diabetes mellitus, smoking, previous history of cerebrovascular accident, and dyslipidemia were strong predictors of peripheral arterial disease. Key word: peripheral arterial disease , acute coronary syndrome, hypertension, diabetes mellitus.